Penerapan Metode Analytical Hierarchy Process pada Rekomendasi Keputusan Pemilihan SIM Card Provider - Subiksa, Gde Brahupadhya; Jasa, Lie (Jurnal Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i03.P01, 2018)
Abstract —SIM card provider is the center of mobile telecommunication such as telephones, texting, Internet or Blackberry messenger. Lately, the SIM card business development is be marked more kinds of SIM card offered by the provider company with various brands, features and facilities. This causes consumers find it difficult to choose the SIM card that suits their needs such as the phone call need, texting need, Internet and Blackberry package, and bonus that the consumer wants. From the problems above, consumer need a decision support system that can gives SIM card recommendation which suits the consumer’s needs. The SIM card provider decision-making selection can be complex because of the multiple purposes of consumer. One of the tools that are suitable to use for SIM card sorting priority is Analytic Hierarchy Process (AHP) that is developed by Thomas L. Saaty. The final result from this thesis is a system of SIM card provider selection decision-making support which suits with the consumer’s needs. The system is tested with data collection by using questionnaire, which aims to obtain data that is more accurate about the usefulness of the system that has been created. Data collection are through the 30 respondents who tried the system from the user side and 5 respondents who filled out questionnaires from the administrator side. The results of the data collection and analysis of data collected declare that this system has its deficiency, especially the difficulty of priority weighting of both.